2017
DOI: 10.3390/geosciences7020043
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Systematics of Coalbed Gas during Desorption and Production

Abstract: The stable carbon isotope ratios of coalbed methane (CBM) demonstrate diagnostic changes that systematically vary with production and desorption times. These shifts can provide decisive, predictive information on the behaviour and potential performance of CBM operations. Samples from producing CBM wells show a general depletion in 13 C-methane with increasing production times and corresponding shifts in δ 13 C-CH 4 up to 35.8. Samples from canister desorption experiments show mostly enrichment in 13 C for meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…In this way, the calculated isotope fractionation was similar to the results of the coal canister method [12]. Determined isotope enrichment ε = −3% for the methane release neared the −2% value for the methane desorption from coal [12,22] and the experimental values from Reference [9] (−1.6 to −2.8% ). The study referred to in Reference [8] reported values from −3.3 to −1.3 % (−4 % as a maximum for coal and mudstone).…”
Section: Carbon Isotope Fractionation During the Sample Degassingsupporting
confidence: 67%
See 2 more Smart Citations
“…In this way, the calculated isotope fractionation was similar to the results of the coal canister method [12]. Determined isotope enrichment ε = −3% for the methane release neared the −2% value for the methane desorption from coal [12,22] and the experimental values from Reference [9] (−1.6 to −2.8% ). The study referred to in Reference [8] reported values from −3.3 to −1.3 % (−4 % as a maximum for coal and mudstone).…”
Section: Carbon Isotope Fractionation During the Sample Degassingsupporting
confidence: 67%
“…Results from diffusion modeling in Reference [11] were also similar. However, the secondary process as desorption could have had a significant effect on isotope fractionation, as was observed during coal bed gas production experiments [22]. We supposed that such secondary processes modified our ethane isotope fractionation, which was higher than literature values.…”
Section: Carbon Isotope Fractionation During the Sample Degassingmentioning
confidence: 59%
See 1 more Smart Citation
“…Individual data points from this study are shown as diamonds ( n = 31). The observed ranges for fermentative (green) and hydrogenotrophic (blue) mcr -based methanogenesis pathways and geological methane sources (red) were taken from reference 93 , although we note that these boundaries are not absolute (see, e.g., reference 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…The heterogeneity of isotopic signatures from coal mining activities in the USCB reflects the geological complexity of the area. Secondary processes (desorption, diffusion or oxidation) also influence the CH 4 isotopic composition, and depend on external parameters such as physical characteristics of the coal reservoirs and the soil layers (Niemann and Whiticar (2017)). These represent additional difficulties as regards the isotopic characterisation of coal associated CH 4 emissions.…”
Section: Isotopic Characterisation Of the Surrounding Sourcesmentioning
confidence: 99%